2021
DOI: 10.1016/j.bpj.2020.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Phosphofructokinase relocalizes into subcellular compartments with liquid-like properties in vivo

Abstract: Although much is known about the biochemical regulation of glycolytic enzymes, less is understood about how they are organized inside cells. We systematically examine the dynamic subcellular localization of glycolytic protein phosphofructokinase-1/PFK-1.1 in Caenorhabditis elegans. We determine that endogenous PFK-1.1 localizes to subcellular compartments in vivo. In neurons, PFK-1.1 forms phase-separated condensates near synapses in response to energy stress from transient hypoxia. Restoring animals to normox… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 112 publications
1
45
0
Order By: Relevance
“…Furthermore, FRAP, GFP florescence recovery, coalesence, and active and passive microrheology experiments have revealed that over time, even the condensates that start displaying a liquid-like state can 'mature' (i.e., change their material properties) and transition to gels or soft glasses 23,51,67,68 . Matured condensates display reduced fusion propensities and longer recovery times after photobleaching 7,29,35,[67][68][69][70][71][72] , which suggest that the diffusion of molecules within is significantly reduced. Several factors have been proposed as key drivers for the liquid-to-solid transition of condensates, including altered salt-concentration or temperature 51,73 , post-translational modifications 36,74 , protein mutations 34,75,76 , and, most prominently, protein folding and misfolding events [77][78][79][80][81][82] .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, FRAP, GFP florescence recovery, coalesence, and active and passive microrheology experiments have revealed that over time, even the condensates that start displaying a liquid-like state can 'mature' (i.e., change their material properties) and transition to gels or soft glasses 23,51,67,68 . Matured condensates display reduced fusion propensities and longer recovery times after photobleaching 7,29,35,[67][68][69][70][71][72] , which suggest that the diffusion of molecules within is significantly reduced. Several factors have been proposed as key drivers for the liquid-to-solid transition of condensates, including altered salt-concentration or temperature 51,73 , post-translational modifications 36,74 , protein mutations 34,75,76 , and, most prominently, protein folding and misfolding events [77][78][79][80][81][82] .…”
Section: Introductionmentioning
confidence: 99%
“…In C. elegans, hypoxia was found to rapidly induce the formation of foci-containing glycolytic enzymes at presynaptic sites in neurons in order to meet the energetic requirements of synaptic signalling [ 129 ]. Furthermore, various human cancer cell lines—but not normal cells—have been found to form small aggregates of glycolytic enzymes (comprising liver-type PFK-1, FBPase, pyruvate kinase M2, and phosphoenolpyruvate carboxykinase-1) even in the presence of oxygen [ 130 ].…”
Section: Potential Alternative Metabolic Adaptations To Survive Hypoxia In Hif-1 Deficiencymentioning
confidence: 99%
“…Yet, the biological relevance of the hypothesized metabolon has remained controversial, mainly because of the lack of studies examining the dynamic distribution of these enzymes in vivo. However, very recently Colón-Ramos and coworkers, using a hybrid microfluidic-hydrogel device and Caenorhabditis elegans as model organism, have proven that phosphofructokinase, that is diffusely localized in the cytosol, can dynamically re-localize into biomolecular condensates in response to transient energy stress [48]. They further determined that these condensates formed in vivo exhibited liquid-like properties, including drop-like shapes due to surface tension, fluidity due to deformations, and fast internal rearrangements, overall suggesting LLPS as the mechanism underlying the formation of these structures, which were previously ruled out to be SGs by the authors of this report [48].…”
Section: Phase Transition: a Spontaneous Process Harnessed By Living Mattermentioning
confidence: 99%
“…However, very recently Colón-Ramos and coworkers, using a hybrid microfluidic-hydrogel device and Caenorhabditis elegans as model organism, have proven that phosphofructokinase, that is diffusely localized in the cytosol, can dynamically re-localize into biomolecular condensates in response to transient energy stress [48]. They further determined that these condensates formed in vivo exhibited liquid-like properties, including drop-like shapes due to surface tension, fluidity due to deformations, and fast internal rearrangements, overall suggesting LLPS as the mechanism underlying the formation of these structures, which were previously ruled out to be SGs by the authors of this report [48]. Of interest, a systematic study examining hundreds of yeast metabolic enzymes involved in intermediary metabolism identified the widespread reorganization of these proteins into reversible assemblies upon nutrient starvation [49], suggesting that dynamic compartmentalization into condensates via LLPS could represent an extended regulatory strategy.…”
Section: Phase Transition: a Spontaneous Process Harnessed By Living Mattermentioning
confidence: 99%